2014
DOI: 10.1007/s11060-014-1566-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for older adults with glioblastoma: radical treatment, palliative treatment, or no treatment at all?

Abstract: The incidence of glioblastoma in older adults has increased over the last few decades. Current treatment includes surgery, radiotherapy, and chemotherapy, but optimal disease management remains a matter of debate. Both standard (60 Gy in 30 daily fractions) and hypofractionated radiotherapy (30-40 Gy in 10-15 daily fractions) have been employed with a similar survival benefit. Recent randomized studies indicate that chemotherapy with the alkylating agent temozolomide is a safe and effective therapeutic option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The question is whether these patients should be treated with a comparably aggressive combined treatment, palliative radiotherapy plus supportive care, or with best supportive care (BSC) including corticosteroids alone. In 2007, a randomized trial compared BSC with vs. without 50 Gy of radiotherapy in patients ≥70 years of age with glioblastoma (WHO grade IV) or anaplastic astrocytoma (WHO grade III) (3,18,19). The trial was stopped after an interim analysis of 85 patients (81 with glioblastoma).…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether these patients should be treated with a comparably aggressive combined treatment, palliative radiotherapy plus supportive care, or with best supportive care (BSC) including corticosteroids alone. In 2007, a randomized trial compared BSC with vs. without 50 Gy of radiotherapy in patients ≥70 years of age with glioblastoma (WHO grade IV) or anaplastic astrocytoma (WHO grade III) (3,18,19). The trial was stopped after an interim analysis of 85 patients (81 with glioblastoma).…”
Section: Discussionmentioning
confidence: 99%
“…The alternative treatment for elderly GBM patients primarily includes hypofractionated RT (HRT), where larger fractions of radiation are administered over a shorter period of time compared with standard RT (6). In certain cases, concurrent TMZ has been added to HRT, based on the superior outcomes reported with the Stupp protocol (7,8), although it has not yet been established that combining HRT with concurrent TMZ is superior to HRT alone (9).…”
Section: Introductionmentioning
confidence: 99%
“…During the interpretation of the results of the present study, its limitations need to be considered that include the retrospective study design (risk of hidden biases) and the comparably small sample size. Moreover, the extent of resection was previously reported to be significantly associated with survival in patients with GBM (32,33). Since our previous study showed only a trend for such an association, this factor was not included in the present score (13).…”
Section: Discussionmentioning
confidence: 97%